PENGARUH KOMUNIKASI DAN KUALITAS PELAYANAN TERHADAP KINERJA PERAWAT DI RUMAH SAKIT BHAYANGKARA PALEMBANG - Hadiwijaya, Hendra (Universitas Pendidikan Ganesha, 2018)
This study aims to determine and analyze the influence of communication and service quality on the performance of nurses at Bhayangkara Hospital Palembang. Sample of research is nurse of Bhayangkara Palembang Hospital counted 110 respondents by using purposive sampling method. The analysis of this research using Structural Equation Modeling (SEM), which is operated through Lisrel Program. The results showed that Communication Variables and Service Quality have a positive and significant impact on the Performance of Nurse Hospital Bhayangkara Palembang. Communication Variables more dominant influence on the Performance of Nurse Hospital Bhayangkara Palembang in comparison of service quality variable